Evaluation of thermoregulation of horses (Equus caballus) submitted to two methods of post-exercise cooling, in hot and humid climate conditions, in the Eastern Amazon - Lisboa, Bruna Rafaela Ferreira; Silva, Jamile Andréa Rodrigues da; Silva, Welligton Conceição da; Barbosa, Antônio Vinícius Corrêa; Silva, Lilian Kátia Ximenes; Lourenço-Júnior, José de Brito (Frontiers in Veterinary Science, 2023)
The research aimed to evaluate the thermoregulation of horses submitted to two methods of cooling after exercise, in conditions of hot and humid climate of the Eastern Amazon. The experiment was conducted at Centro Hípico, Ananindeua, Pará (latitude 1°23'33.4" south and longitude 48°24'27.6" west), for 15 days. Ten castrated male horses of the Brasileiro breed were used. Horse Riding (BH), which were exercised with a pre-established protocol in riding arena and track, for 30 minutes. After the exercise, the animals were divided into two groups for application of the treatments, which were two cooling methods, such as bath with water at room temperature (about 25ºC) and hyper-cooling method (6 to 9ºC). During the experimental period, air temperature (TA) and relative humidity (RH) data were recorded and the Temperature and Humidity Index (ITU) was calculated. Data from rectal temperature (TR), heart rate (HR), respiratory rate (RR) and skin temperature (TP) of the animals were also measured at three moments: before exercise, after exercise and after applying the cooling methods. The adaptability index used was the Benezra Thermal Comfort Index (ICB). After the application of the cooling techniques in the animals, the AT and UTI were higher and the highest RH values were found before the exercise (87.21%). The highest TR, FR, HR, TP and ICB values were observed after exercise. There was no significant difference (P>0.05) between cooling methods. There was a highly significant and positive correlation (P<0.01) between all physiological variables (TR, FR, HR, PT) and the Iberian Index with AT and UTI and negative with RH (P<0.01), thus demonstrating the influence of the environment on the thermoregulation of animals. It is concluded that the physiological variables of horses are altered after physical exercise. It was found that there is no advantage in using the HR, since for the application of this method it is necessary to have costs for its manufacture.